2007
DOI: 10.1266/ggs.82.281
|View full text |Cite
|
Sign up to set email alerts
|

The GTP-binding protein YqeH participates in biogenesis of the 30S ribosome subunit in Bacillus subtilis

Abstract: Bacterial genome sequencing has revealed a novel family of P-loop GTPases that are often essential for growth. Accumulating evidence suggests that these proteins are involved in biogenesis of the 30S or 50S ribosomal subunits. YqeH is a member of this Obg/Era GTPase family, with its function remains to be uncovered. Here, we present results showing that YqeH is involved in the 30S subunit biogenesis in Bacillus subtilis. We observed a reduction in the 70S ribosome and accumulation of the free 50S subunit in Yq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 40 publications
1
46
0
Order By: Relevance
“…Both YlqF and YqeH are essential for cell growth in Bacillus subtilis. They have been shown to bind [␣- 32 P]GTP (31), and GTPase activity was demonstrated for YqeH (32). The B. subtilis yqeH mutant is lethal, whereas reduced YqeH expression increases chromosomal replication (31).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both YlqF and YqeH are essential for cell growth in Bacillus subtilis. They have been shown to bind [␣- 32 P]GTP (31), and GTPase activity was demonstrated for YqeH (32). The B. subtilis yqeH mutant is lethal, whereas reduced YqeH expression increases chromosomal replication (31).…”
mentioning
confidence: 99%
“…The B. subtilis yqeH mutant is lethal, whereas reduced YqeH expression increases chromosomal replication (31). YqeH participates in the biogenesis of the 30 S ribosome subunit (32) and assists in 50 S ribosome assembly (33). A high throughput screen in yeast found that a distant homolog of YqeH interacts with a ribosomal protein (31,34,35).…”
mentioning
confidence: 99%
“…Gradients-The deficit of the 15 S rRNA in the mtg3 ts mutant grown under restrictive conditions and previous evidence implicating the YqeH GTPase of Bacillus subtilis in assembly of the 30 S ribosomal subunit (29,30) suggested that Mtg3p might play a similar role in yeast mitochondria. This was also consistent with detection of normal sedimenting 54 S subunit in the different mtg3 mutants examined.…”
Section: Sedimentation Of Large and Small Subunit Proteins In Sucrosementioning
confidence: 89%
“…Although mtg3 null and ts mutants grown at the nonpermissive temperature displayed a reduction in the 54 S subunit, this is related to the high percentage of o/Ϫ cells in the strains. Last, YqeH, an Mtg3p homologue of B. subtilis has also been implicated in assembly of the 30 S but not the 50 S ribosomal subunit of this organism (29,30). The bacterial protein has been shown to bind to 30 S subunit (45) but its function in assembly has yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Its maturation involves cleavage and trimming of the precursors of rRNA, modification of the base or ribose of rRNA, assembly of ribosomal proteins, and proper folding (Lu and Inouye 1998;Kaczanowska and Rydén-Aulin 2007;Wilson and Nierhaus 2007). These processes require the help of a considerable number of trans-acting factors in the cell (Jones and Inouye 1996;Bylund et al 1998;Inoue et al 2003;Kaczanowska and Rydén-Aulin 2004;Sato et al 2005;Karbstein 2007;Loh et al 2007), although a functional ribosomal particle can be reconstituted from the components in vitro without any trans-acting factors (Held et al 1974;Holmes and Culver 2005).…”
Section: Introductionmentioning
confidence: 99%